(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article examines the role of logical tasks in the development of students’ thinking. The main types of logical tasks, their educational value, and their influence on cognitive development have been analyzed. Particular attention is paid to the formation of critical, analytical, and creative thinking, as well as the practical aspects of using logical tasks in the educational process. Teachers’ methodological recommendations aimed at increasing the effectiveness of their application are presented. The conclusion is drawn about the importance of logical tasks as a tool for developing key competencies necessary for successful professional activity.